Parental involvement in children’s homework: a literature review - Falanga, Konstantina; Gonida Eleftheria Ν. (Psychology: the Journal of the Hellenic Psychological Society, 2022)
Parental involvement in children’s homework takes a variety of forms with distinct qualitative characteristics. The present review paper discusses the role of quality of parental homework involvement, the predictors of specific involvement forms adopted by parents and their learning outcomes for children. According to relevant literature, parent motivational beliefs, efficacy beliefs, beliefs about children’s efficacy, and parent affect predict different forms of involvement which, in turn, are associated with different motivational, emotional, and learning outcomes. Specifically, autonomy granting and support in tackling homework challenges, opposite to controlling involvement practices, contributes to the development of children’s motivational beliefs towards learning, high academic competence beliefs, and positive emotions. The present review emphasizes the complexity of the relationships among the plethora of parent and children variables in the field of homework, identifies future research directions and provides recommendations for practice targeting the promotion of children’s learning and school achievement.